Widespread distribution of kiwifruit bacterial canker caused by the European Pseudomonas syringae pv. actinidiae genotype in the main production areas of Portugal - Marsilio RENZI (Phytopathologia Mediterranea, 2012)
In Portugal, in 2010, after the first recorded occurrence of Pseudomonas syringae pv. actinidiae (Psa) in a few kiwifruit orchards, and following subsequent records of suspected symptoms at the beginning of 2011, an extensive survey concerning Psa was carried out. One hundred and sixty-two samples (trunks, twigs, leaves, flowers, buds) presenting symptoms were collected from the main Portuguese kiwifruit areas and submitted to phyto-bacteriological analyses to verify possible relationships between the symptoms/damage observed and the presence of Psa in kiwifruit orchards. The results confirmed the widespread presence of the pathogen in the main production areas of Portugal, where different Actinidia spp. cultivars are grown. Genetic investigations revealed that all the Psa strains detected belong to the European genotype. Preliminary considerations concerning pathogen dissemination are made.